Turning the Knobs: The Impact of Post-translational Modifications on Carbon Metabolism - Matiolli, Cleverson C.; Soares, Rafael Cavém; Alves, Hugo L. S.; Abreu, Isabel A. (Frontiers in Plant Science, 2022)
Plants rely on the carbon fixed by photosynthesis into sugars to grow and reproduce. However, plants often face non-ideal conditions caused by biotic and abiotic stresses. These constraints impose challenges to managing sugars, the most valuable plant asset. Hence, the precise management of sugars is crucial to avoid starvation under adverse conditions and sustain growth. This review explores the role of post-translational modifications (PTMs) in the modulation of carbon metabolism. PTMs consist of chemical modifications of proteins that change protein properties, including protein-protein interaction preferences, enzymatic activity, stability, and subcellular localization. We provide a holistic view of how PTMs tune resource distribution among different physiological processes to optimize plant fitness.